Management of Village Fund Allocation in Realizing Good Governance in Pematang Tujuh Village, Pontianak - Dini Lestary; Lilis Suryani (Future Science, 2024)
This study aims to examine the management of the Village Fund Allocation in Pematang Tujuh Village, Rasau Jaya Subdistrict, Kubu Raya Regency, by implementing the principles of Good Governance. This research uses a case study method with a descriptive qualitative approach, employing data collection techniques such as observation, interviews, and documentation. The study involved three respondents as sources of information. The findings reveal that the planning stage adheres to the Ministry of Home Affairs Regulation No. 113 of 2014, starting with Dusun Meetings and Village Development Planning Meetings (Musrenbangdes), involving the active participation of the Pematang Tujuh Village community. The Village Institution's involvement in the preparation of the Village Medium-Term Development Plan (RPJM Desa) and the Village Government Work Plan (RKP Desa) is discussed in Musrenbangdes meetings, subsequently organized by a special team. The results of these meetings are then displayed on announcement boards and billboards. In the implementation stage, the management of the Village Fund Allocation is carried out by a management team responsible for the Accountability Report (SPJ), involving the Pematang Tujuh Village community in the execution of activities. All activities related to budget implementation are announced on the website and notice boards.